G.M. Fredlender’s Review on M.M. Bakhtin’s “To the Issues of the Methodology of the Aesthetics of Verbal-artistic Creativity” - Oleg E. Osovskiy; Svetlana A. Dubrovskaya (Studia Litterarum)
The article presents G. Friedlander’s peer-review on M. Bakhtin’s manuscript of the collection of works. This is the first publication of G. Friedlander’s text written at December 26, 1973. It provides the detailed analysis and assessment of Bakhtin’s book that was published in 1975 under the title “Questions of Literature and Aesthetics.” Highly assessing the scholar’s contribution to Russian literary criticism, the reviewer underlines the innovative nature of the previously unpublished articles in the collection. Bakhtin’s attitude to the “formal school” and his criticism of “material aesthetics” are also important to him. It allows G. Friedlander to name Bakhtin among the most authoritative opponents of structuralism and other schools of Western literary criticism. The most significant to the reviewer are Bakhtin’s discoveries in the field of historical poetics, primarily in the history and theory of the novel. One of the points of G. Friedlander’s disagreement was the interpretation of Gogol’s laughter in the context of Rabelais’ work. The publication of the review is accompanied by the preface, which reconstructs the context of the reception of Bakhtin’s ideas in the late Soviet era, indicates the points of dialogue between G. Friedlander and M. Bakhtin in the 1950s–1970s. The publication is provided with notes.